Efficacy and safety of iGlarLixi versus IDegAsp: Results of a systematic literature review and indirect treatment comparison. Issue 12 (31st August 2021) - Home, Philip D.; Mehta, Roopa; Hafidh, Khadija A. S.; Gurova, Olesya Y.; Alvarez, Agustina; Serafini, Paul; Pourrahmat, Mir‐Masoud
Abstract: Aim: To assess the efficacy and safety of iGlarLixi, a fixed‐ratio combination of basal insulin glargine 100 U/mL and lixisenatide (glucagon‐like peptide‐1 receptor agonist) versus IDegAsp, a co‐formulation of basal insulin degludec 100 U/mL with rapid‐acting insulin aspart. Materials and Methods: A systematic literature search of randomized controlled trials (RCTs) was performed. Outcomes from eligible RCTs were compared by an indirect treatment comparison using a Bayesian framework. Subanalyses of Japanese and international trials were performed. Results: Eight RCTs (duration 26‐30 weeks) were included. Mean difference in HbA1c change with iGlarLixi exceeded that for IDegAsp: −0.64 (95% credible interval −1.01, −0.28) %‐units (−7.0 [−11.0, −3.1] mmol/mol) for all trials, −0.39 (−0.55, −0.23) %‐units (−4.3 [−6.0, −2.5] mmol/mol) for international, and −0.88 (−1.11, −0.64) %‐units (−9.6 [−12.1, −7.0] mmol/mol) for Japanese trials. HbA1c target achievement (<7.0%‐units [<53 mmol/mol]) was greater for iGlarLixi in all trials (odds ratio 2.50 [1.06, 5.56]) and Japanese trials (2.17 [1.27, 3.70]), but not in international trials (2.17 [0.42, 11.11]). Analyses suggesting differences in mean postmeal self‐measured plasma glucose were significantly lower by 1.0‐2.0 mmol/L (18‐36 mg/dL) with iGlarLixi in all analyses. Bodyweight change was more favourable (1‐2 kg) for iGlarLixi versus IDegAsp for all analyses ( P  < 0.05). Comparisons of hypoglycaemia were inconclusive owing to differences in definitions between studies. Adverse events were more frequent with iGlarLixi because of gastrointestinal intolerance. Conclusions: iGlarLixi appears to offer clinical benefit in glucose control and bodyweight change in people needing both basal and meal‐time intervention.